A two-front nutritional environment fuels colorectal cancer: perspectives for dietary intervention. (February 2022) - Alderweireldt, Elien; Grootaert, Charlotte; De Wever, Olivier; Van Camp, John
Abstract : Colorectal cancer (CRC) develops and progresses in a nutritional environment comprising a continuously changing luminal cocktail of external dietary and microbial factors on the apical side, and a dynamic host-related pool of systemic factors on the serosal side. In this review, we highlight how this two-front environment influences the bioenergetic status of colonocytes throughout CRC development from (cancer) stem cells to cancer cells in nutrient-rich and nutrient-poor conditions, and eventually to metastatic cells, which, upon entry to the circulation and during metastatic seeding, are forced to metabolically adapt. Furthermore, given the influence of diet on the two-front nutritional environment, we discuss dietary strategies that target the specific metabolic preferences of these cells, with a possible impact on colon cancer cell bioenergetics and CRC outcome. Highlights: Colon epithelial and CRC cells are exposed to a unique two-front nutritional environment. (Cancer) cells acquire nutrients from both sides for their bioenergetic and/or biosynthetic pathways. The nutritional composition of the two fronts defines the tumor microenvironment, the preferred metabolic routes, and the rate of each energetic pathway. Cancer cell bioenergetics may be steered by well-designed dietary interventions that can improve patient outcome.